A 53-Year-Old Male with Relapsed Diffuse Large B-Cell Lymphoma on Chemotherapy with a New Leg Lesion - Connie R. Shi; Sarah N. Robinson; Avery LaChance; Martin C. Mihm Jr.; Daniela Kroshinsky (Dermatopathology, 2017)
Patients with underlying malignancy who develop new skin findings while acutely ill often require skin biopsy for histologic evaluation and/or culture to reach a diagnosis. Here, we present the case of a 53-year-old male with relapsed diffuse large B-cell lymphoma on chemotherapy who developed new skin lesions on the leg. On exam, there were 2 nickel-sized, erythematous to violaceous round plaques with central necrotic cores on the right lower leg with relatively nonspecific clinical features for which the initial differential diagnosis was broad. Consensus on a diagnosis was reached upon histologic evaluation of his skin biopsy in the context of his clinical setting. This diagnosis led to a change in treatment plan, with subsequent clinical improvement.